Internalization of Local Wisdom Values of the Hajat Laut Rancabuaya Tradition as a Social Studies Learning Source - Anggraeni, Leni; Dahlena, Alni; Agustina, Risma; Ramdani, Mamur (SAHUR Journal, 2023)
The cultural environment as a learning resource for students is one way to maintain and introduce local wisdom. The purpose of this study is to shape the character of students through the values and local wisdom of the Hajat Laut tradition, which is the culture closest to them. This research method uses a qualitative approach with an ethnographic design. Data collection techniques include triangulation (observation, interviews, and documentation). The results of this research are: 1) The tradition of sea celebration is a fisherman's celebration activity that has been carried out since ancient times by the ancestors. 2) The implementation of the sea ritual tradition is supported by positive activities that have cultural and social values that can be used as community guidelines for interaction. 3) The values contained in the Hajat Sea tradition are religious values, cultural values, mutual cooperation values, artistic values, social care values, recreational values, economic values, and the value of love for the homeland and cultural history. 4) Internalization of the competence of local wisdom values of the Hajat Laut tradition, namely by correlating these values to those concerned as well as the material contained in textbooks. Therefore, the tradition of going to sea can be used as a source of social studies learning, which has a correlation with the natural environment, social environment, cultural environment, and economic environment contained in social studies subject matter.